2017
DOI: 10.1373/clinchem.2016.261495
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cardiac Troponin in Cardiovascular Diseases Other Than Acute Coronary Syndrome

Abstract: BACKGROUND Increased cardiac troponin concentrations in acute coronary syndrome (ACS) identify patients with ongoing cardiomyocyte necrosis who are at increased risk. However, with the use of more precise assays, cardiac troponin increases are commonly noted in other cardiovascular conditions as well. This has generated interest in the use of cardiac troponin for prognostic assessment and clinical management of these patients. In this review, we have summarized the data from studies investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 85 publications
0
61
0
3
Order By: Relevance
“…Although cTn is commonly increased in HF, routine cTn measurements are currently not recommended unless there is suspicion of underlying acute coronary syndrome (ACS) [14]. Therefore, and as ST2 concentrations are not increased in ACS [15], a multimarker approach including ST2 may overcome limitations related to cTn as single biomarker for risk-stratification, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Although cTn is commonly increased in HF, routine cTn measurements are currently not recommended unless there is suspicion of underlying acute coronary syndrome (ACS) [14]. Therefore, and as ST2 concentrations are not increased in ACS [15], a multimarker approach including ST2 may overcome limitations related to cTn as single biomarker for risk-stratification, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study in the setting of ST-elevation acute MI, beta-1 adrenoceptor autoantibodies were associated with adverse outcomes (being an independent predictor of major adverse cardiovascular events) (39). Evermore sensitive assays for cardiac troponins have demonstrated that these biomarkers may be detectable in several clinical conditions, as well as in a significant proportion of healthy subjects (59,60). Anticardiac troponin autoantibodies have also been described in different settings (namely in healthy subjects and after MI) (6).…”
Section: Discussionmentioning
confidence: 99%
“…This may have resulted in sampling bias, with the selection of younger patients with fewer comorbidities. The new medical protocol that was implemented when hs-cTnT cutoff was lowered to the 99th percentile stated that the only indication of a hs-cTnT test is suspicion of acute cardiac damage [22] and alerted the attending physician to the fact that old age [6,15], decreased kidney function [23][24][25] and heart failure [26,27] can result in false positive hs-cTnT results. This could be an explanation behind decreased hs-cTnT sampling frequency Recorded heart diagnosis except for hypertension among patients that were not analyzed with hs-cTnT during the ED visit or hospital stay.…”
Section: Discussionmentioning
confidence: 99%